Bacia Hidrográfica do Rio Formoso: a dinâmica da turbidez da água, causas e efeitos - Ingrid Maroli Vidal dos Santos Clemente (2025)
This study evaluated how changes in land use and occupation, especially agricultural expansion over pasture areas, impacted turbidity and water quality in the Bonito region - MS, famous for tourism in rivers with crystal-clear waters. It was assumed that the advance of agriculture, combined with conservationist practices and climate events, intensified river turbidity, harming water transparency and local tourism. The general objective was to analyze the dynamics of turbidity, its causes and effects in the Formoso River Sub-Basin. The methodology involved field data collection, including water measurements and sampling, complemented by secondary data on land use and occupation obtained from MapBiomas. The collected samples were analyzed in the laboratory to determine major elements (cations and anions) by ion chromatography, identification of dissolved organic matter by UV-Vis spectrophotometry and quantification of total suspended solids (TSS) by the gravimetric method. The results showed that, between 2013 and 2022, agriculture grew by 108.6% while pastures decreased by 43.5%, increasing surface runoff and the contribution of sediments and nutrients to rivers, raising turbidity mainly after rain events. The study highlighted three distinct turbidity situations: (1) high turbidity values accompanied by high concentrations of total suspended solids (TSS), related to surface runoff; (2) high turbidity with low TSS, associated with dissolved organic matter from subsurface runoff, possibly linked to the adoption of the no-till system associated with the terracing technique; and (3) moderate turbidity in dry periods, linked to the precipitation of calcium carbonate (whiting phenomenon), possibly resulting from the lowering of the water table and intensification of chemical weathering. Thus, it was concluded that the replacement of pastures by agriculture/soybean cultivation altered the hydrogeochemical and hydrosedimentary dynamics, compromising water quality and threatening the sustainability of aquatic ecosystems and local tourism.